2021
DOI: 10.1093/geronb/gbab144
|View full text |Cite
|
Sign up to set email alerts
|

Rich and Balanced Experiences of Daily Emotions Are Associated With Activity Diversity Across Adulthood

Abstract: Objectives Studies demonstrate the association between diverse emotions and health. However, we know little about how these emotions are related to activities in daily life. This study examined whether the diversity of daily activities (“activity diversity”) is associated with the diversity of both positive and negative daily emotions (“emodiversity”) in adulthood. We also examined if these associations differed by age. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…However, studies have yet to explore how emotional granularity may be impacted by shifting what people encounter when they go about their daily lives. Building on other recent research, for example, future research could examine how emotional granularity is impacted by increased variation in daily activities (Lee et al, 2021) or in spatial and sociodemographic environments (Heller et al, 2020). Such work has the potential to not only establish novel, behavior-based interventions, but to reveal causal paths linking experiential diversity to emotional granularity.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, studies have yet to explore how emotional granularity may be impacted by shifting what people encounter when they go about their daily lives. Building on other recent research, for example, future research could examine how emotional granularity is impacted by increased variation in daily activities (Lee et al, 2021) or in spatial and sociodemographic environments (Heller et al, 2020). Such work has the potential to not only establish novel, behavior-based interventions, but to reveal causal paths linking experiential diversity to emotional granularity.…”
Section: Discussionmentioning
confidence: 96%
“…From this perspective, greater variation in experience could result in more elaborated (i.e., rich, diverse) emotion concepts: exposure to a broader range of sensorimotor inputs and social dynamicsthat is, the contexts and activities encountered over timemight allow the brain to construct predictions that are better tailored to the situation at hand, increasing emotional granularity. At the same time, a richer and more diverse set of emotion concepts could contribute to greater variation in the types and frequencies of everyday experiences (Lee et al, 2021). Concepts are known to shape how events are perceived, and this process may extend to experience of emotion (e.g., Richmond & Zacks, 2017).…”
mentioning
confidence: 99%
“…Given that older adults tend to avoid emotional situations that contain high levels of arousal (Sands & Isaacowitz, 2017), the situations that they are more familiar with may be less likely to contain high levels of arousal and therefore allow older adults to leverage their strengths at processing and regulating emotions. However, it has been suggested that older adults who engage in more diverse activities in daily life experience more rich and balanced emotions throughout their day-to-day life (Lee et al, 2022). It is possible that being familiar with a variety of contexts rather than remaining in the same situations (e.g., staying at home consistently) enables individuals to experience differentiated and rich positive emotions.…”
Section: Familiarity and Higher Emotion Differentiation And Emotional...mentioning
confidence: 99%
“…Consistent with a conservation model of stress (Hobfoll, 1989), high stressor diversity theoretically functions as a resource that confers differential well-being (Koffer et al, 2016). Following techniques used in the natural sciences to assess the biodiversity of ecosystems (Magurran, 2004; Morin, 1999), researchers have used measures of diversity to assess a variety of social and psychological phenomena, including racial and ethnic diversity (Budescu & Budescu, 2012), behavioral flexibility (Ram et al, 2012), population genetics (Sherwin, 2010), community social networks (Li et al, 2015), emotional diversity (Ong et al, 2018; Quoidbach et al, 2014; Urban-Wojcik et al, 2022), and activity diversity (Lee et al, 2018, 2022).…”
Section: Applications Of Daily Process Formulations Of Resilience To ...mentioning
confidence: 99%